Study and treatment of installations against bacterial corrosion - Dekhili Nourelhouda; Chala Abdelouahad (University Of Eloued جامعة الوادي, 2020)
In this work, we study the effects of bacterial growth on pipelines in the south of Algeria (bacterial corrosion of distribution and transport pipes). In addition, we study efficacy of inhibitor (NORUST 720) and biocide (biocide 2 CHIMEC 7660) used to treatment this problem. This problem of bacterial corrosion is frequently encountered in the production and injection circuits during the extraction of the oil. Hence, it leads to the formation of deposits on the inner surface of the pipes which causing a risk of clogging. First, we analyse the water separated from petroleum to detect the presence of Sulphate-Reducing Bacteria (SRB). Second, we study the behaviour of steel in an environment contaminated by SRB. For this purpose, we use, the pH, SEM, and EDX machines a analysing the surface of the samples which allow us to observe and knowledge the deposition chemical composition formed on the surface of the samples.
Intervention
Keywords: Corrosion; Bacterial Corrosion; Sulphate-Reducing Bacteria; treatment; Steel N 80